1987
DOI: 10.1111/j.1476-5381.1987.tb11343.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of Ca2+ channels by palmitoyl carnitine, a putative endogenous ligand

Abstract: Palmitoyl carnitine, a lipid metabolite which accumulates in cytoplasmic membranes during ischaemia, has been shown to resemble the Ca2+ channel activator, Bay K 8644, in K+‐depolarized smooth muscle. Palmitoyl carnitine caused concentration‐dependent (1–1000 μmol l−1) augmentations in the sensitivity to Ca2+ of K+‐depolarized taenia preparations from the guinea‐pig caecum. The (±)‐isomer was equieffective with the (–)‐isomer, whereas carnitine was ineffective and palmitic acid relaxed the tissues. The shift t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 51 publications
0
30
1
Order By: Relevance
“…Recently, we have shown that exogenous LPC can induce delayed afterdepolarizations and triggered rhythms in vitro (36), effects stimulated by catecholamines. Long-chain acylcarnitines can activate calcium channels in cardiac muscle and smooth muscle (7)(8)(9). Accordingly, the antiarrhythmic influence of POCA seen in the present study is likely to involve amelioration of both reentrant and non-reentrant mechanisms responsible for arrhythmogenesis in ischemic myocardium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, we have shown that exogenous LPC can induce delayed afterdepolarizations and triggered rhythms in vitro (36), effects stimulated by catecholamines. Long-chain acylcarnitines can activate calcium channels in cardiac muscle and smooth muscle (7)(8)(9). Accordingly, the antiarrhythmic influence of POCA seen in the present study is likely to involve amelioration of both reentrant and non-reentrant mechanisms responsible for arrhythmogenesis in ischemic myocardium.…”
Section: Discussionmentioning
confidence: 82%
“…Long-chain acylcarnitines, one class of amphipathic metabolites, activate calcium channels in cardiac (7,8) and smooth muscle myocytes (8,9). Accordingly, they may potentiate the increase in cytosolic calcium associated with arrhythmogenesis in ischemic myocardium (10).…”
Section: Introductionmentioning
confidence: 99%
“…Palmitoyl carnitine and other acylcarnitines have been shown to be endogenous in vitro ligands for calcium channel activation. 18,19 This activation of myocardial calcium channels has been used to explain the positive inotropic effects of palmitoyl carnitine on chick heart cell aggregates. 20 It is therefore possible in our model that the IV L-carnitine is being transported into myocytes and bound to free fatty acids with acetyl-CoA to form higher concentrations of acylcarnitines.…”
Section: Discussionmentioning
confidence: 99%
“…This does render screening difficult at times. For example, exquisitely potent compounds acting at one site may appear to have no effect when assessed on a different allosteric, or an orthosteric, site, because the apparent zero effect is a result of negative and positive allosteric effects that are revealed by changing temperature and other experimental variables (Spedding and Mir, 1987); hence the need to define the experimental conditions when quantifying and classifying allosteric compounds. In general, two useful themes in the pharmacological approach to demonstrating allostery are 1) the ability to identify saturability of effect and 2) the ability to demonstrate probe dependence.…”
Section: Experimental Approaches For Validating An Allosteric Inmentioning
confidence: 99%